MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN MELALUI PENGGUNAAN PEMBELAJARAN METODE SQ3R PADA SISWA KELAS V SD NEGERI 2 MALINO - Rahma Ashari Hamzah (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
This study aims to improve reading comprehension skills of fifth grade students of SD Negeri 2 Malino through the use of the SQ3R learning model with reference to 2 criteria, namely student learning outcomes and observation of student and teacher activities. This type of research uses classroom action research, with a design activity of 2 meetings with 2 cycles. Data collection techniques used were tests and observations, then analyzed using percentage statistics. The percentage of completeness obtained is in the first syllable of the Survey stage 57.69% (C), the Questions stage 53.84% (K), the Read stage 53.84% (K), the Recall stage 46.15% (K), and the Reviuw 30.76% (K). Meanwhile, in cycle II the percentage of completeness obtained is the Survey stage 84% (B), the Questions stage 84.61% (B), the Read stage 76.92% (B), the Recall stage 76.92% (B), and the Reviuw 84.61% (B). The results showed that learning to read comprehension using the SQ3R model has shown a significant improvement so it is appropriate to use it in reading comprehension learning material in class V SD Negeri 2 Malino.Keywords: Reading comprehension, SQ3R